A novel solar PV/T driven photocatalytic multifunctional system: Concept proposal and performance investigation. (August 2022) - Xia, Xiaokang; Gu, Tao; Fan, Miaomiao; Chen, Haifei; Yu, Bendong
Abstract: This article proposes a novel PV/T driven liquid-photocatalytic-purification multifunctional system that combines photocatalytic purification technology with PV/T technology. The experiments on the effects of concentration and depth of TiO2 nanofluids layer, and air bubble rate on the electrical, dissolving and photocatalytic oxidation of formaldehyde performance were conducted. Then the energy analysis on the proposed system in a typical day was investigated. The following results are obtained. (1) Both the concentration and depth of TiO2 nanofluids layer have very significant effect on the electrical performance. A certain amount of TiO2 nanoparticles in TiO2 nanofluids could improve the formaldehyde solubility in water. (2) The photocatalytic oxidation rate increases with the formaldehyde concentration of 0.01–0.15 mg/L (3) The photocatalytic process could be divided into three stages: accumulation area, rapid reaction area and complete reaction area. While the air bubbling can merge the accumulation area and rapid reaction area, and thus enhances the photocatalytic process. (4) In a typical day, the proposed system has the reduction of 22.9% and 17.0% in thermal efficiency and electrical efficiency compared with conventional PV/T water system, while it has an additional efficient sterilization time of 2.5 h. Highlights: Solar PV/T driven photocatalytic multifunctional system. Effects of concentration, depth of TiO2 nanofluids on photovoltaic performance. Effects of bubble rate, TiO2 concentration on formaldehyde dissolving, degradation performance. Energy comparison of proposed system with conventional PV/T water system.